Decomposition analysis of safflower production in India: Decomposition analysis of safflower production in India - S B RAMYA LAKSHMI; K C GUMMAGOLMATH; PRIYANKA PATRA (Journal of Oilseeds Research, 2020)
The present study was an attempt to analyze the growth performance of total oilseeds in India and relativecontribution of area and yield on production of safflower in particular using secondary data. The results indicated that during the study period (2005-06 to 2017-18) area under almost all the crops except soybean had declined whereas production declined only in case of sunflower (-13.40 %), safflower (-7.41 %) and niger seed (-2.85 %). Further, a detailed district wise analysis of safflower revealed that the area was the major contributor (56.94 %) for the decline in production of safflower in Belgaum district. The contribution of productivity was remarkable in Bidar district (572 %). In Period–I, productivity effect was high in the case of Osmanabad (114 %) and Parbhani (110 %) districts and in Period- II, interaction effect was high in the case of Hingoli district (566.20 %).